Rectangular dielectric structures for the wakefield acceleration experiments in KIPT - Galaydych, K.V.; Kiselev, V.A.; Markov, P.I.; Naboka, A.M.; Onishchenko, I.N.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2013)
At the Kharkov Institute of Physics and Technology is planned experimental test of the basic principles of the multi-bunch multi-mode dielectric wakefield accelerator. For this purpose we carried out a series of calculations of wakefield excitation and dynamics of the drive and witness bunches in rectangular structures with a dielectric sub-strate. For optimization two rectangular vacuum waveguides of R32 (72.14 × 34.04 mm) and R26 (86.36 × 43.18 mm) which were filled with the dielectric covering two any opposite metal walls of a waveguide were chosen. As possible dielectric Alumina, Cordierite, or Teflon were tested. It was supposed that the structure will be energized by train of electron bunches (bunch repetition frequency is 2.805 GHz) of 4.5 MeV energy, average current is 1 A. As the candidate for operating mode the LSM-wave or the LSE-wave, with frequency to equal the bunch repetition frequency or its doubled frequency were tested. The gradient of an accelerating field, small transverse deflection (or divergence) of drive and witness bunches were the main criteria of optimization. As a result of optimization we propose some dielectric structures for future wakefield experiments in KIPT.